2022
DOI: 10.1155/2022/6129817
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Role of Bioinformatics Analysis in Early Differential Diagnosis of Ovarian Cancer

Abstract: In order to solve the problem of early differential diagnosis of ovarian cancer, this paper proposes the role of bioinformatics analysis in early differential diagnosis of ovarian cancer. This method uses bioinformatics methods to mine the existing data in the tumor database and obtain tumor-related molecules. It is an efficient method to obtain effective biomarkers, screen signal pathway molecules, and reveal the internal mechanism of tumor occurrence and development. Using this method can greatly improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Meta-analysis plays a crucial role in bioinformatics by integrating the outcomes of multiple studies and applying analysis to the data (Zhang et al, 2022). It allows for the comparison of outcomes from various studies, identification of models within the results, recognition of interesting associations that may arise (Sun et al, 2023).…”
Section: Bioinformatic Studiesmentioning
confidence: 99%
“…Meta-analysis plays a crucial role in bioinformatics by integrating the outcomes of multiple studies and applying analysis to the data (Zhang et al, 2022). It allows for the comparison of outcomes from various studies, identification of models within the results, recognition of interesting associations that may arise (Sun et al, 2023).…”
Section: Bioinformatic Studiesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%